Extra-Articular Hip Resection and Reconstruction with Custom Acetabular Resection Guide and Implants in a Case of High-Grade Spindle Cell Sarcoma of the Proximal Femur: A Case Report. Issue 3 (16th July 2020) - Manrique, Jorge; Schiffman, Corey J.; Chan, Albert D.; Olsen, David; Thompson, Matthew J.
Abstract : Case: A 29-year-old man was admitted with acute atraumatic left hip pain and inability to bear weight. Subsequent workup revealed an intracapsular pathologic fracture of the femoral neck secondary to a high-grade spindle cell sarcoma. A unique method of extra-articular resection and reconstruction using a 3-dimensional (3D)-printed custom cutting jig and a custom acetabular component was pursued. Wide margins were achieved without violating the joint capsule but preserving pelvic integrity, allowing a return to an active lifestyle. Conclusion: Three-dimensional-printed custom resection guides and implants can help achieve adequate resection margins while preserving pelvic integrity and function.